On the follow-up efforts of long-period transiting planet candidates detected with Gaia astrometry. Issue 2 (27th January 2023) - Sozzetti, A; Giacobbe, P; Lattanzi, M G; Pinamonti, M
ABSTRACT: The class of transiting cold Jupiters, orbiting at ≳0.5–1.0 au, is to-date underpopulated. Probing their atmospheric composition and physical characteristics is particularly valuable, as it allows for direct comparisons with the Solar system giant planets. We investigate some aspects of the synergy between Gaia astrometry and other ground-based and space-borne programs for detection and characterization of such companions. We carry out numerical simulations of Gaia observations of systems with one cold transiting gas giant, using Jovian planets around a sample of nearby low-mass stars as proxies. Using state-of-the-art orbit fitting tools, we gauge the potential of Gaia astrometry to predict the time of transit centre T c for the purpose of follow-up observations to verify that the companions are indeed transiting. Typical uncertainties on T c will be on the order of a few months, reduced to several weeks for high astrometric signal-to-noise ratios and periods shorter than ∼3 yr. We develop a framework for the combined analysis of Gaia astrometry and radial-velocity data from representative ground-based campaigns and show that combined orbital fits would allow to significantly reduce the transit windows to be searched for, down to about ±2 weeks (2–σ level) in the most favourable cases. These results are achievable with a moderate investment of observing time (∼0.5 nights per candidate, ∼50 nights for the top 100 candidates), reinforcing the notion that Gaia astrometric detections of potentially transiting cold giant planets, starting with Data Release 4, will constitute a valuable sample worthy of synergistic follow-up efforts with a variety of techniques.